Collaborative Governance dalam Tata Kelola Pariwisata-Desa (Studi Pariwisata-Desa â€œBumiaji Agrotourismâ€ di Kota Wisata Batu) - Matthoriq, Matthoriq; Zauhar, Soesilo; Hermawan, Romy (Jurnal Ilmiah Administrasi Publik, 2021)
The objective of this research is examines the role of collaborative governance in rural tourism development, especially in the tourist area of "Bumiaji Agrotourism" in Tourist City of Batu. The rapid development of tourism in Batu is still dominated by the artificial tourism destinations, often the highlight in relation to the equitable distribution of welfare and sustainability of tourist development. Until today, the efforts of local governments and communities by presenting a variety of new icon types of community-based tourism destinations in Batu City do not provide assurance that tourism will remain exsist and suistain due to resource limitations in each actor. In accordance with Good Tourism Governance (GTG), tourism management efforts can no longer be charged only to one of the actors. Collaborative governance approach can be used as an alternative solution, especially in rural tourism development in Tourist City of Batu to strengthen the character of tourist destinations as well as tourism network buildings.